2018
DOI: 10.1002/cpe.4446
|View full text |Cite
|
Sign up to set email alerts
|

Emotion detection from EEG recordings based on supervised and unsupervised dimension reduction

Abstract: Summary In recent years, researchers have been trying to detect human emotions from recorded brain signals such as electroencephalogram (EEG) signals. However, due to the high levels of noise from the EEG recordings, a single feature alone cannot achieve good performance. A combination of distinct features is the key for automatic emotion detection. In this paper, we present a hybrid dimension feature reduction scheme using a total of 14 different features extracted from EEG recordings. The scheme combines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…With many features, the size of the learning set required for modeling must be proportionally large, which takes a long time to categorize. Accordingly, various manifold learning approaches such as PCA (principal components analysis), maximal revision minimum redundancy (mRMR) [ 9 ], and various feature space reduction techniques such as selecting features using F-scores have been used to address the issue [ 10 ]. The existing stress analysis methods lack in an effective features dimensionality reduction technique to improve performance of a subsequent classifier.…”
Section: Introductionmentioning
confidence: 99%
“…With many features, the size of the learning set required for modeling must be proportionally large, which takes a long time to categorize. Accordingly, various manifold learning approaches such as PCA (principal components analysis), maximal revision minimum redundancy (mRMR) [ 9 ], and various feature space reduction techniques such as selecting features using F-scores have been used to address the issue [ 10 ]. The existing stress analysis methods lack in an effective features dimensionality reduction technique to improve performance of a subsequent classifier.…”
Section: Introductionmentioning
confidence: 99%
“…The original article presented the DEAP database reported a 62.0 % for low-high arousal and a 57.6% for lowhigh valence classification. A recent study reported an improvement with 74.3 % for low-high arousal and 77.2% for low-high valence classification tasks [12]. Another study reported the first results from a static connectivity analysis incorporating the richness of spatiotemporal EEG brain activity from 1 min into a single functional brain network.…”
Section: Introductionmentioning
confidence: 99%
“…It can analyse the main influencing factors from multiple contexts, reveal the essence of entities, and simplify complex problems. Liu et al proposed a hybrid dimension featurereduction scheme using 14 different features extracted from EEG recordings [24]. To reorder the combined features into max-relevance with the labels and min-redundancy of each feature, maximum relevance minimum redundancy (mRMR) was applied.…”
Section: Introductionmentioning
confidence: 99%